Islamization of Science in The Perspective of Fazlur Rahman: Reconstructing Qur'anic Epistemology - Firdaus, Nazilatul Fatihah; Iksan, I (Al'ulum Jurnal Pendidikan Islam, 2026)
The Islamization of science has become an important issue in efforts to integrate science with the values contained in the Qur'an. This study focuses on the thinking of Fazlur Rahman, who proposed a normative and applicative approach through the double movement method. This study used a library research method with an epistemological approach. The results of the study show that Fazlur Rahman emphasizes the importance of moral responsibility in the development of science so that it does not become a disaster for humanity. According to Fazlur Rahman, the Islamization of science is not merely a matter of labeling science as “Islamic,” but rather a process of epistemological reconstruction based on rationality, ethics, and context. This concept aims to avoid dogmatization and secularization in science. However, Fazlur Rahman wants to make Islam the answer to various social, political, economic, and cultural problems that occur in the modern era.